The Poem about the Prophet’s Death in Mozambique – Swahili as a Transregional Language of Islamic Poetry - Vierke, Clarissa; Mutiua, Chapane (Journal for Islamic Studies, 2023)
This article throws light on the hitherto neglected Swahili Islamic poetry from Mozambique. By concentrating on the Poem about the Prophet’s Death, locally called Nazajina, our contribution shows specific adaptations to local language and recitation practices while at the same time reflecting on Swahili as a transregional language of Islamic poetry that links places on the Swahili coast that are distant from each other. Manuscripts of the poem can be found all along the East African Swahili coast. We will follow its distribution from the Lamu archipelago in the north to Mozambique, in the trail of the Sufi reform movements of the nineteenth century.